Modeling EFL learners’ engagement: Serial mediation of autonomy support, enjoyment, and ideal L2 self - Hanwei Wu (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Engagement plays a critical role in enhancing English as a Foreign Language (EFL) learning. Therefore, investigating the factors that influence engagement is essential. This study explores the mechanisms through which engagement is shaped by key factors among EFL learners, within the framework of Self-Determination Theory (SDT). Specifically, the focus is on autonomy support, enjoyment, and ideal L2 self. A total of 413 EFL learners from diverse colleges participated in an online survey, where these constructs were measured using four validated scales. Structural Equation Modeling (SEM) via AMOS 24 was employed for data analysis. The results indicated that autonomy support, enjoyment, and ideal L2 self directly and positively predicted learner engagement. Furthermore, autonomy support indirectly influenced engagement through enjoyment, ideal L2 self, or both. These findings highlight the significance of these factors in fostering EFL learner engagement and offer valuable insights for enhancing EFL education and guiding future research on engagement dynamics.